SPATIAL LOCATION OF SOLID WASTE DUMPSITES AND COLLECTION SCHEDULING USING THE GEOGRAPHIC INFORMATION SYSTEMS IN BAUCHI METROPOLIS, NIGERIA - Ogwuche, Jonathan Ali (European Scientific Journal, ESJ, 2013)
﻿﻿﻿This study examines the application of Geographic Information Systems in determining the spatial location of solid waste dump sites and collection scheduling in Bauchi metropolis. The study used the field survey and survey research design to acquire spatial and non-spatial data respectively. The spatial data were obtained using a Quickbird image and map of Bauchi State, as well as GPS, and ESRI ArcGIS 9.2 software. The non-spatial data on household size, waste generation and disposal were obtained from the interview of 38 households sampled in the area. The study obtained data on household solid waste generation, disposal as well as collection schedule, and identified hotspots of solid waste dumpsites in the area. The study revealed that the average household size is 9, daily solid waste generated per household is 6.11kg, and per person is 0.80kg. While 40% of the solid wastes generated are managed by BASEPA, 30% are indiscriminately dumped in unauthorized spots in the area. The map of the area showing the spatial location of the identified hot spots of the dumpsites was produced. The study recommends the employment of the integrated solid waste management system that requires geospatial information if sustainable solid waste management in urban areas is to be achieved.